The Role of Digital Story in Promoting Preventive Health Concepts among Primary Stage Students - Alomoush, Reem AbdElkareem (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The study aims to investigate the role of digital stories in promoting the concepts of preventive health among primary stage students. The study tool used to conduct this study is a questionnaire that contains 30 items focusing on six areas, namely health food, risk management, personal health, environmental health, first aid, and physical health. The study sample consists of 218 male and female teachers. The study concluded that digital stories have an average role in promoting the concepts of preventive health in general among primary stage students from the viewpoint of class teachers. The study recommended the necessity of honing the skills of teachers of the primary stage regarding preventive health concepts. In addition, it is recommended that seminars and training courses should be conducted to teach teachers how to present such concepts to students using digital stories.